2018
DOI: 10.12659/ajcr.907383
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia Presenting with Liver Infiltration and Severe Lactic Acidosis

Abstract: Patient: Male, 58Final Diagnosis: Acute lymphoblastic leukemiaSymptoms: Chest pain • fatigue • loss of appetite • shortness of breathMedication: —Clinical Procedure: Liver biopsy and bone marrow biopsySpecialty: HematologyObjective:Rare diseaseBackground:Type-B lactic acidosis is a rare complication of solid tumors and hematological malignancies. It occurs secondary to Warburg effect, when glucose metabolism in cancer cells switches from the oxidative pathway to the glycolytic pathway. Malignant lactic acidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Cancer cells including leukemic blasts use glucose to produce a severely elevated level of lactic acid by switching the oxidative pathway to the glycolytic pathway even in the presence of oxygen, whereas in normal cells glucose generates lactate in anaerobic conditions (Warburg, 1956). Accumulation of lactic acid is associated with poor prognosis of ALL (Sayyed et al, 2018), and hyperglycemia is found in about 10% ALL patients during chemotherapy treatment, who are associated with risk of infection and poorer survival (Panigrahi et al, 2016). In this study, we used high glucose to stimulate this activation in the blasts.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells including leukemic blasts use glucose to produce a severely elevated level of lactic acid by switching the oxidative pathway to the glycolytic pathway even in the presence of oxygen, whereas in normal cells glucose generates lactate in anaerobic conditions (Warburg, 1956). Accumulation of lactic acid is associated with poor prognosis of ALL (Sayyed et al, 2018), and hyperglycemia is found in about 10% ALL patients during chemotherapy treatment, who are associated with risk of infection and poorer survival (Panigrahi et al, 2016). In this study, we used high glucose to stimulate this activation in the blasts.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases the liver can utilize the Cori cycle to counteract lactic acidosis. 6 The development of persistent lactic acidosis may indicate neoplastic liver infiltration 7,8 ; however, in patients with intact liver function with no evidence of metastases there is still much to explore about what predisposes these patients to lactic acidosis. Also the presence of high levels of lactate may reflect the poor prognostic outcome of the malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumors, the EMT process enhances the metastatic potential converting polarized epithelial cells into non-polarized mesenchymal cells thus promoting cell mobility, invasion and resistance to apoptotic stimuli (48)(49)(50). In hematological malignancies, the blasts move from BM into peripheral blood and colonize distant sites such as liver and spleen, a process reminiscent of EMT in metastatic solid tumors (51)(52)(53). Moreover, it has been recently demonstrated that EMT transcription factors are critical in promoting leukemia and lymphoma progression (6, 18).…”
Section: Discussionmentioning
confidence: 99%